Digital governance and innovative management in the public and private sectors: strategic, social, and humanistic dimensions - Buryk, Zoriana (Revista Administração em Diálogo - RAD, 2025)
This special issue examines the multifaceted nature of digital governance across public, private, and social sectors. It highlights how digital transformation goes beyond technological efficiency to shape cultural, economic, and institutional dynamics. The articles explore themes such as organizational digitalization, human capital development, green management, public-sector innovation, transparency, and legal mechanisms of accountability. Special attention is given to Ukraine’s experience, illustrating how digital tools can strengthen institutional trust, service quality, and resilience during crises. The issue emphasizes that digital modernization is not solely technical—it must integrate ethical governance, professional capacity-building, social capital, and environmental responsibility. Together, the contributions demonstrate how emerging technologies—ranging from ERP and CRM evolution to blockchain, IoT, and big data—can enhance transparency, resource efficiency, and citizen engagement, reinforcing governance systems for sustainable development.